Web-based exercise versus supervised exercise for decreasing visceral adipose tissue in older adults with central obesity: a randomized controlled trial - Ballin, Marcel; Hult, Andreas; Björk, Sabine; Lundberg, Emmy; Nordström, Peter; Nordström, Anna (BMC geriatrics, 2020)
Background Visceral adipose tissue (VAT) is a strong risk factor for cardiovascular disease and increases with age. While supervised exercise (SE) may be an effective approach, web-based exercise (WE) have other advantages such as being more readily accessible. Therefore, we evaluated the effects of WE on VAT, body composition and cardiometabolic risk markers in centrally obese older adults and compared the effects of WE to SE. We also explored the feasibility of WE. Methods In a randomized controlled trial conducted in Umeå, Sweden during January 2018 – November 2018, N = 77, 70-year-old men and women with central obesity (> 1 kg VAT for women, > 2 kg for men) were randomized to an intervention group ( n = 38) and a wait-list control group ( n = 39). The intervention group received 10 weeks of SE while the wait-list control group lived as usual. Following a 10-week wash-out-period, the wait-list control group received 10 weeks of WE. The primary outcome was changes in VAT. Secondary outcomes included changes in fat mass (FM), lean body mass (LBM), blood lipids, fasting blood glucose. Additionally, we explored the feasibility of WE defined as adherence and participant experiences. Results WE had no significant effect on VAT ( P = 0.5), although it decreased FM by 450 g (95% confidence interval [CI], 37 to 836, P < 0.05). The adherence to WE was 85% and 87–97% of the participants rated aspects of the WE intervention > 4 on a scale of 1–5. Comparing SE to WE, there was no significant difference in decrease of VAT (Cohen’s δ effect size [ES], 0.5, 95% CI, − 24 to 223, P = 0.11), although SE decreased FM by 619 g (ES, 0.5, 95% CI, 22 to 1215, P < 0.05) compared to WE. Conclusions Ten weeks of vigorous WE is insufficient to decrease VAT in centrally obese older adults, but sufficient to decrease FM while preserving LBM. The high adherence and positive experiences of the WE intervention implies that it could serve as an alternative exercise strategy for older adults with central obesity, with increased availability for a larger population. Trial registration ClinicalTrials.gov ( NCT03450655 ), retrospectively registered February 28, 2018.